12 impossible daredevil stunts - Bell, Samantha (Bell, Samantha. Incredible., 2020)
Profiles twelve daredevils and stunt men and women who have achieved famous feats--from African American daredevil female pilot Bessie Coleman to Harry Houdini escaping from shackles and a straightjacket while hanging upside down. Includes a glossary.